2020
DOI: 10.1002/mnfr.201900942
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction is a Key Pathway that Links Saturated Fat Intake to the Development and Progression of NAFLD

Abstract: Non-Alcoholic fatty liver disease (NAFLD) is the most common form of liver disease and is characterized by fat accumulation in the liver. Hypercaloric diets generally increase hepatic fat accumulation, whereas hypocaloric diets decrease liver fat content. In addition, there is evidence to suggest that moderate amounts of unsaturated fatty acids seems to be protective for the development of a fatty liver, while consumption of saturated fatty acids (SFA) appears to predispose toward hepatic steatosis. Recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 108 publications
1
47
0
Order By: Relevance
“…Further study is needed to investigate offspring liver steatosis in a sexually dimorphic manner. In addition, there has been a growing interest regarding the association between NAFLD and the type of HFD; previous studies showed that moderate intake of unsaturated fatty acids had a protective effect on the development of NAFLD and that SFAs seemed to be prone to hepatic steatosis (47). Therefore, as the rate-limiting enzyme that catalyzes the rate-limiting step for the conversion of SFA into MUFA, inhibition of SCD1 activity might ameliorate the metabolic disorders with less adverse effects caused by HFD in the future (48).…”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to investigate offspring liver steatosis in a sexually dimorphic manner. In addition, there has been a growing interest regarding the association between NAFLD and the type of HFD; previous studies showed that moderate intake of unsaturated fatty acids had a protective effect on the development of NAFLD and that SFAs seemed to be prone to hepatic steatosis (47). Therefore, as the rate-limiting enzyme that catalyzes the rate-limiting step for the conversion of SFA into MUFA, inhibition of SCD1 activity might ameliorate the metabolic disorders with less adverse effects caused by HFD in the future (48).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that our multivariate regression showed that there was a weak positive correlation between GSD and NAFLD in hypercholesterolemia patients, and even based on the above, we tend to agree with the notion that NAFLD, possibly including hypertriglyceridemia, might be a secondary actor in overweight/obesity and hypercholesterolemia patients after eliminating blood pressure and diabetes (blood sugar, insulin resistance). These are the following supporting facts: rst, NAFLD is typically characterized by atherogenic dyslipidemia featuring higher triglyceride levels with greater circulating very-low-density lipoprotein levels, lower levels of dense LDL-c and low levels of dysfunctional HDL-c (41). A recent report supported the notion that hypercholesterolemia is a major risk factor for the initiation and development of NAFLD (42), resulting from high-cholesterol diet, lipase de ciencies and liver in ammation (43,44).…”
Section: Discussionmentioning
confidence: 85%
“…Based on this observation, it could be speculated that NAFLD, possibly including hypertriglyceridemia, might be a secondary actor in overweight/obesity and hypercholesterolemia patients after eliminating blood pressure and diabetes (blood sugar, insulin resistance). These are the following supporting facts: first, NAFLD is typically characterized by atherogenic dyslipidemia featuring higher triglyceride levels with greater circulating very-low-density lipoprotein levels, lower levels of dense LDL-c and low levels of dysfunctional HDL-c (41). A recent report supported the notion that hypercholesterolemia is a major risk factor for the initiation and development of NAFLD (42), resulting from high-cholesterol diet, lipase deficiencies and liver inflammation (43,44).…”
Section: Discussionmentioning
confidence: 85%
“…High fat diet and saturated fat may cause hepatic steatosis. Saturated fat changes mitochondrial structure and function and leads to the development and progression of NAFLD [41].…”
Section: Discussionmentioning
confidence: 99%